Implementation of Character Education in Online Learning of Elementary School in Ternate City, Indonesia (Eurasian Journal of Learning and Academic Teaching, 2022)
This research was carried out in order to find out the implementation of character education in online learning class III SD Negeri 1 Ternate City. The type of research used is qualitative descriptive.   The data collected using observation methods, interviews and documentation that successfully collected a number of realities related to the implementation of character education in online learning.  Then the data in the analysis uses the techniques of data collection, data reduction, data presentation and conclusions to determine the results of character formation through the implementation of character education in online learning of class III SD Negeri 1 Ternate City.  The results of this study show that the implementation of character education in online learning has an impact on the formation of student character, including religious, disciplined, responsible, independent and politeness all that is seen from the beginning of character education students begin to change slowly